'Alone in a Crowd': Teacher-Level and Pupil-Level Hidden Curricula and the Theoretical Limits of Teacher-Pupil Relationships - Daniel Whittaker (MDPI AG, 2024)
This essay aims to explore the theoretical limitations that hidden curricula-hidden normative values, beliefs, and knowledge that are often considered problematic-place on our understanding of teacher-pupil relationships. It applies Habermas' theory of communicative action-synonymous with mutual understanding and predicated on his concept of the lifeworld-to analyse hidden curricula. It finds that hidden curricula limit teachers' comprehension of teacher-pupil relationships dependent on pupils' responses to teacher-level hidden curricula. Where they respond with compliance, pupils limit expressions of their subjectivity; conversely, where they reject teacher-level hidden curricula, pupils' subjective lifeworlds are already disrupted by them. Both responses impede teachers' understanding of teacher-pupil relationships. In addition, pupil-level hidden curricula, which are often asymmetrical and oriented in response to teacher-level hidden curricula, present another barrier to teachers unveiling hidden curricula and the subjectivities of teacher-pupil relationships. In effect, pupil-level hidden curricula render teachers 'alone in a crowd'. Finally, I argue that systematically examining hidden curricula represents strategic action-communicative action's counterpoint-and colonisation of pupils' lifeworlds. While hidden curricula present significant theoretical limitations to understanding teacher-pupil relationships, teachers might use this as a 'pedagogical hinge', freeing them from the unknowable and uncontrollable to a more practical view of teacher-pupil relationships.